PENGUJIAN KEAWETAN ALAMI PAPAN PARTIKEL DARI CAMPURAN LIMBAH BATANG SORGHUM DAN SERUTAN KAYU - Andrianta Ginting; Irawati Azhar; Apri Heri Iswanto (Program studi Kehutanan USU, 2015)
Sorghum stalk bagasse is potential raw materials to particleboard manufacture. In the previous research, sorghum bagasse particleboard had weakness matter in modulus of elasticity, internal bond and thickness swelling properties. Wood shaving mixture will be expected to improve of those properties. The objective of this research was to evaluate the effect of wood shaving added to improve mechanical properties of particleboard. Wood shaving type was added in particleboard manufacturing consist of Meranti, Cempedak, Mahoni, and Durian. Sorghum bagasse and wood shaving ratio in this research was 50/50 (%w/w). Amount of 10% urea formaldehyde (UF) resin used for binding. Hot pressing process was conducted in 1300C temperature for 10 minute and 30 kg cm-2 pressure. The result showed that, the thickness swelling (TS) does not fulfill of requirement JIS A 5908 (2003). Cempedak and Mahoni wood shaving mixture resulted of lower the TS value than control and other wood shaving mixture. In generally, wood shaving and sorghum bagasse mixture result in increasing of internal bond properties. Cempedak wood shaving resulted the best of bending properties than control and other mixture. Keyword : sorghum stalk, wood shaving, particleboard